2016
DOI: 10.1051/metal/2016035
|View full text |Cite
|
Sign up to set email alerts
|

DEM simulation of particle descending velocity distribution in the reduction shaft furnace

Abstract: -Reduction shaft furnace is a promising alternative to blast furnace ironmaking. The particle descending velocity distribution has a great influence on the shaft furnace, which directly affects the production index and further the shaft furnace normal smelting. Therefore, a three-dimensional model (3D) is established based on the discrete element method (DEM) and computation fluid dynamic (CFD). The effect of the gas flow in the shaft furnace, the height, the diameter and the bosh angle of the shaft furnace on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The intricate fluid dynamics associated with granular flows have been extensively investigated. [12][13][14][15][16] Wu et al [17] performed an experimental and theoretical investigation of the flow characteristics of solid particles within a 2D moving bed. Their study revealed that factors such as the shape, size, and rest angle of the solid particles have a significant impact on the resulting flow pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The intricate fluid dynamics associated with granular flows have been extensively investigated. [12][13][14][15][16] Wu et al [17] performed an experimental and theoretical investigation of the flow characteristics of solid particles within a 2D moving bed. Their study revealed that factors such as the shape, size, and rest angle of the solid particles have a significant impact on the resulting flow pattern.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Since the shape of lump ore is nonspherical and random, and the difference in shape will affect the charge compliance to a great extent, it is necessary to consider the difference in charge distribution and movement behavior in the shaft furnace due to the shape of the lump ore. Currently, the discrete element method (DEM) has been widely used to study the basic solid flow behavior in iron-making processes such as blast furnace, [10][11][12] smelting processes such as COREX, [13][14][15][16] and direct reduction processes such as MIDREX. [7] In addition, in a previous study, Yu et al [17] verified that DEM can predict the flow of irregular and spherical particles.…”
Section: Introductionmentioning
confidence: 99%
“…This method can generate detailed microdynamic information of individual particles, such as particle velocity and interaction forces between particles, which is key for understanding the flow of burden materials in ironmaking process. Thus, DEM has been applied to study solid flow in a shaft furnace in smelting reduction process, such as dynamic burden distribution, particle descending velocity, effect of screws on solid flow, and the effect of Areal Gas Distribution (AGD) beams on solid flow . These studies provide useful information on solid flow in shaft furnace.…”
Section: Introductionmentioning
confidence: 99%